PARTISIPASI MASYARAKAT DALAM PENCEGAHAN KEBAKARAN LAHAN GAMBUT (STUDI KASUS MASYARAKAT PEDULI API DI KECAMATAN RASAU JAYA, KABUPATEN KUBU RAYA) - Yuhana, Wiji; AM, Iskandar (Universitas Tanjungpura, 2017)
Every year, especially during the dry season, Rasau Jaya subdistrict is always shrouded in smoke resulting from land and forest fires. Since 2004, the Government of West Kalimantan Province has encouraged community participatoin in prevention and control of fires, especially in areas prone to forest fires which become a major cause of smog in the area Rasau Jaya, but the causes of fires in agricultural land are still significant and have not yielded optimal result. Based on this fact, this research aims to find out the root of the problem and the causes of the ineffectiveness of the participation of the fires aware community in prevention of land fire. This research is a descriptive study. The main data in this study were obtained through interviews with saurces who know and are involved in effots of forest fires, and supported by the data of fieled observations The data were analyz using chi squere. The results showed that: (1) participation community MPA and non MPA in the prevention of land fire in the Kecamatan Rasau Jaya, Kab. Kubu Raya. every tall in prevention of land fire. (2) Relationship MPA and non MPA in the prevention of land fire, level knowledge, employment, and education, not relationship in the level cosmopolitan relationship in the level participation prevention of land fire. (3) using the prevention of land fire for community MPA revitalizing comonity MPA, with the government, for it non MPA controlled land burning.Keywords: Fire Ware Community, Peat Land, Rasau Jaya, Society Participation